Immune Profile of the Normal Maternal-Fetal Interface in Rhesus Macaques and Its Alteration Following Zika Virus Infection - Moström, Matilda J.; Scheef, Elizabeth A.; Sprehe, Lesli M.; Szeltner, Dawn; Tran, Dollnovan; Hennebold, Jon D.; Roberts, Victoria H. J.; Maness, Nicholas J.; Fahlberg, Marissa; Kaur, Amitinder (Frontiers in Immunology, 2021)
The maternal decidua is an immunologically complex environment that balances maintenance of immune tolerance to fetal paternal antigens with protection of the fetus against vertical transmission of maternal pathogens. To better understand host immune determinants of congenital infection at the maternal-fetal tissue interface, we performed a comparative analysis of innate and adaptive immune cell subsets in the peripheral blood and decidua of healthy rhesus macaque pregnancies across all trimesters of gestation and determined changes after Zika virus (ZIKV) infection. Using one 28-color and one 18-color polychromatic flow cytometry panel we simultaneously analyzed the frequency, phenotype, activation status and trafficking properties of αβ T, γδ Τ, iNKT, regulatory T (Treg), NK cells, B lymphocytes, monocytes, macrophages, and dendritic cells (DC). Decidual leukocytes showed a striking enrichment of activated effector memory and tissue-resident memory CD4+ and CD8+ T lymphocytes, CD4+ Tregs, CD56+ NK cells, CD14+CD16+ monocytes, CD206+ tissue-resident macrophages, and a paucity of B lymphocytes when compared to peripheral blood. t-distributed stochastic neighbor embedding (tSNE) revealed unique populations of decidual NK, T, DC and monocyte/macrophage subsets. Principal component analysis showed distinct spatial localization of decidual and circulating leukocytes contributed by NK and CD8+ T lymphocytes, and separation of decidua based on gestational age contributed by memory CD4+ and CD8+ T lymphocytes. Decidua from 10 ZIKV-infected dams obtained 16-56 days post infection at third (n=9) or second (n=1) trimester showed a significant reduction in frequency of activated, CXCR3+, and/or Granzyme B+ memory CD4+ and CD8+ T lymphocytes and γδ Τ compared to normal decidua. These data suggest that ZIKV induces local immunosuppression with reduced immune recruitment and impaired cytotoxicity. Our study adds to the immune characterization of the maternal-fetal interface in a translational nonhuman primate model of congenital infection and provides novel insight in to putative mechanisms of vertical transmission.